Letter to the editors - Jian Zu; Wendi Wang; Bo Zu (Mathematical Biosciences and Engineering)
Our paper Evolutionary dynamics of prey-predator systems with Holling type IIfunctional response, recently published in MBE (pp. 221-237, vol. 4, 2007), heavilydraws on earlier work by Michael Doebeli and Ulf Dieckmann:  &nbspDoebeli, M & Dieckmann, U. (2000). Evolutionary branching andsympatric speciation caused by different types of ecologicalinteractions. American Naturalist 156: S77-S101, cited as reference[11] in our paper.  &nbsp Dieckmann, U., Marrow, P. & Law, R. (1995).Evolutionary cycling in predator-prey interactions: populationdynamics and the Red Queen. Journal of Theoretical Biology 176:91-102, cited as reference [8] in our paper.